Malay traditional games are never a loss: An emotional reflection of malaysians and immigrants in malaysia - Nasir Yusoff; Kuay Hue San; Rabeta Mohd Salleh; Rohani Ismail; Roslee Ahmad; Audrey Antoine (Editura Universitatii din Oradea, 2024)
Indexed by SCOPUS/ERA